PENILAIAN KINERJA KEUANGAN KOPERASI BERDASARKAN PERATURAN DEPUTI BIDANG PENGAWASAN KEMENTERIAN KOPERASI DAN USAHA KECIL DAN MENENGAH (Studi Pada Koperasi Karyawan â€œTunas Harapanâ€ PT. Bentoel Prima Kabupaten Malang) - Febrianti, Ruby Rantina (Jurnal Ilmiah Mahasiswa FEB, 2017)
TheÂ  Â objectiveÂ  Â ofÂ  Â theÂ  Â studyÂ  Â isÂ  Â toÂ  Â examineÂ  Â theÂ  financialÂ  Â performanceÂ  Â of PT. Bentoel Prima's employee cooperative, Tunas Harapan, during the period of 2013 up to 2015. The research tool used to assess the financial performance is the Regulation No. 06/Per/Dep.6/IVl20l6 issued by the Supervision Deputy of the Ministry of Cooperatives and Small and Medium Enterprises. The regulation covers such research aspects as capital, productive asset, management, efficiency, liquidity, independence and development, and cooperative's identity. This descriptive research attempts to explain the financial performance of the employee cooperative Tunas Harapan with the cooperative's accountability report as the primary data source. The data are collected by document study and interview. The collected data are further analyzed by the ratios contained in the tools. The result of analysis illustrates that the financial performance of PT. Bentoel Prima's employee cooperative Tunas Harapan is "FAIRLY HEALTHY" in 2013 and "HEALTHY" in2014 and2015. Out of seven aspects, management is not used in the research. Out of six research aspects, productive assets quality and cooperative's identity shows that the cooperative has a satisffing result as it obtains maximum score in every ratio for three respective years.Keywords: Capital, Productive Assets Quality, Efficiency, Management, Liquidity, Independence and Development, Cooperative' Identity.Â